Penerapan Verified Carbon Standard (VCS) Berbasis Self Assesment System Guna Mencapai Good Governance: Studi Kasus pada Kantor Dinas Badan Pendapatan Daerah Kabupaten Karawang - Febiyani, Dhea Aulia; Yanti, Yanti; Lasmini, Lilis (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to provide insight on the ways in which the incorporation of a self-evaluation system into municipal tax collecting may have beneficial consequences on the environment of the surrounding area. Standards for the verification of carbon emissions, independent valuation systems, and management organizations that are managed efficiently are some of the items that will be investigated as part of this project. In the Indonesian province of Karawang, this particular field of study must be completed before working in private industry or for the government. The method that was used was a descriptive quantitative one, and the major data analysis was based on the outcomes of an online distribution of a Kuesioner questionnaire to 143 individuals who were involved in the research. According to research, self-evaluation programs have the potential to enhance the delivery of public services and have an effect on the environment, in particular via the reduction of carbon emissions. It is possible that possible improvements to the delivery of public services might lead to improvements in governance for the general populous